Effectiveness of Neural Repatterning-Based Therapy in Reducing Misophonia Symptoms and Physical Reflex Responses in Individuals with Misophonia Disorder - Hashemi, Touraj; Bayrami, Mansour; Mashinchi Abbasi, Naiemeh; Hejazi, Fatemehsoghra (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to determine the effectiveness of neural repatterning-based therapy in reducing misophonia symptoms and physical reflex responses among individuals diagnosed with misophonia disorder.Methods and Materials: This study employed a quasi-experimental single-case design with multiple baselines. The statistical population consisted of individuals with misophonia disorder who attended psychiatric clinics in Tabriz, Iran, in 2025. Four eligible participants were selected through purposive sampling based on the study inclusion criteria. Each participant received eight individual sessions of neural repatterning-based therapy, with each session lasting approximately 60 minutes. Assessments were conducted repeatedly during the baseline, intervention, and follow-up phases. Data were collected using the Misophonia Questionnaire developed by Wu et al. (2014) and the Misophonia Physical Response Scale developed by Dozier (2015). Treatment effectiveness was evaluated through visual analysis of changes across phases, percentage improvement calculations, and the Reliable Change Index to determine whether the observed changes exceeded measurement error and represented clinically meaningful improvement.Findings: Neural repatterning-based therapy produced a clinically significant reduction in misophonia symptoms across the participants. The mean Reliable Change Index for misophonia symptoms was 3.62, exceeding the accepted threshold for reliable clinical change, while the mean percentage improvement was 58.66%. The intervention also significantly reduced physical reflex responses associated with triggering sounds. For physical responses, the mean Reliable Change Index was 2.28, indicating reliable improvement, and the mean percentage improvement reached 62%. The reductions observed during the intervention phase were generally maintained during the follow-up period, supporting the stability of the therapeutic effects.Conclusion: Neural repatterning-based therapy appears to be an effective intervention for reducing both the psychological symptoms of misophonia and the involuntary physical responses elicited by triggering sounds. By modifying maladaptive neural and conditioned response patterns, this approach may help individuals regulate their emotional and bodily reactions to misophonic triggers. The findings support its potential application as a focused clinical intervention for individuals with misophonia, although further controlled studies with larger samples are required.